1995
DOI: 10.1002/apmc.1995.052290101
|View full text |Cite
|
Sign up to set email alerts
|

Melt free‐radical grafting of glycidyl methacrylate onto polypropylene

Abstract: This paper concerns free-radical grafting of glycidyl methacrylate (GMA) onto polypropylene (PP) in the molten state carried out in a batch mixer. This free-radical grafting proceeds very rapidly as it goes to completion within two to three minutes at 200°C. The grafting yield of GMA alone is low and it is greatly enhanced upon addition of styrene as a second monomer with a reduced chain degradation of PP. Homopolymer and copolymer of GMA formed during grafting were quantified. It is suggested that in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 8 publications
1
68
0
1
Order By: Relevance
“…GMA's grafting yields onto PP were also measured by FTIR according to the procedures described elsewhere. 16,18 …”
Section: Determination Of the Amount Of Grafted Gma Onto Epr Or A MIXmentioning
confidence: 98%
See 2 more Smart Citations
“…GMA's grafting yields onto PP were also measured by FTIR according to the procedures described elsewhere. 16,18 …”
Section: Determination Of the Amount Of Grafted Gma Onto Epr Or A MIXmentioning
confidence: 98%
“…16,17 Basically, they were dissolved in boiling xylene and precipitated in acetone to remove unreacted and polymerized GMA. They were then dried in a vacuum oven overnight at 80°C.…”
Section: Determination Of the Amount Of Grafted Gma Onto Epr Or A MIXmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for example, for LDPE-g-IA compositions (8), (14), and (20) (Table I) This assumption should be also taken into consideration when processing experimental data presented in Tables II and III. The reason for the MWD bimodality for LDPEg-IA obtained in dynamic mixing is the raised homogenization degree of the reactive blend and the higher grafted product yield compared with static mixers. The mixer type substantially affefcts the structure of LDPE-g-IA amorphous phase.…”
Section: Discussionmentioning
confidence: 95%
“…The grafting yield of LDPE remains weak (Ͻ10%). Lambla et al 8,9 studied the radical grafting of GMA onto PP in the molten state to compatibilize in situ the PP/PBT blends. They obtained a similar grafting yield (0.8%, determined by FTIR) using conditions close to those used by Liu et al 7 They showed that to multiply the grafting yield of GMA onto PP by a factor of 3 or 4, it is necessary to associate a comonomer such as styrene.…”
Section: Introductionmentioning
confidence: 99%